A novel three-fluorophore system as a ratiometric sensor for multiple protease detection - Okorochenkova, Yana; Porubský, Martin; Benická, Sandra; Hlaváč, Jan (Chemical communications (Cambridge, England), 2018)
A synthetic three-fluorophore system with two enzymatically cleavable linkers has been developed for the simultaneous detection of two proteases in a mixture. The probe was designed to afford single excitation/triple emission ratiometric detection through a fluorescence change during the cleavage of a peptide linker. The developed assays were verified for trypsin and chymotrypsin as the model enzymes.
Keywords: trypsin; fluorescenční barviva; Rhodamines; aminokumariny; rezonanční přenos fluorescenční energie; Phenylalanine; hydrolýza; Aminocoumarins; Enzyme Assays; rhodaminy; fluoresceiny; fluorescence; Chymotrypsin; chymotrypsin; Fluoresceins; Drug Stability; Trypsin; Fluorescent Dyes; fenylalanin; Fluorescence Resonance Energy Transfer; lysin; enzymatické testy; Fluorescence; Lysine; stabilita léku; Hydrolysis